Good Governance and the Sustainable Development of the Niger Delta Region of Nigeria: Assessing the Impact of Government Interventonist Agencies. - Ikenga, Francis A.; Edo, Zephaniah; Ighoshemu, Benedict O. (Journal of Danubian Studies and Research, 2022)
The devastation of the Niger delta environment through oil pollution has occasioned poverty, social unrest, unemployment among the people of the region. It has also threatened the sustainable development of the region and called into question government commitment to good governance. In response, the federal government of Nigeria has over the years established interventionist agencies whose focus is to find lasting solution to the socio-economic problems of the Niger delta region and to ensure its sustainable development. However, in spite of the huge amount appropriated to these agencies, it is believed that their impact on the region has been minimal. This paper, using secondary data anchored on extant literature review interrogates the reason behind their poor performances. Findings shows that among other factors like corruption and projects abandonment, the lack of emphasis in addressing the root cause of the people’s poverty has been a major failure of these agencies. The paper therefore recommends among others, that government through these agencies can have positive impact on the Niger delta by directing resources to pressing area of needs, addressing environmental pollution which is the root cause of crisis in the region instead of spreading thin its resources to projects that have little impacts on the people’s problem.